Equal citizenship for everyone? - Towards the inclusive society, a cross-national comparative study of active citizenship and activation policies for persons with disabilities in Sweden and Japan - - Moriya,Yuko (2011)
This thesis problematizes the exclusion of disabled people in society and their rights. The emphasis of the research is on persons with severe or/ and multiple disabilities who tend not to have capabilities to politically interact with society. They are one of the most marginalized groups among disabled people in numerous aspects while most of them are already excluded in society. This research especially considers how discourses of their citizenship are translated into the context of national policies in Sweden and Japan. Through a comparative analysis, the problematic concept of ‘active-citizenship’ in the active labour market policies and its impact on persons with severe disabilities will be revealed. The aim of this research is to explore how severely disabled people are recognized in the process of policy-making in Sweden and Japan and how the country-particular setting causes difference in establishing their citizenship.
Keywords: persons with severe disabilities; citizenship; active citizenship; activation policy; Sweden; Japan